THE ROLE OF FAMILY SUPPORT, SELF EFFICACY WITH STUDENT RESILIENCE IN COMPLETING THESIS - Kristina Putri Wira; Yarmis Syukur; Neviyarni S; Dina Sukma (RADJA PUBLIKA, 2023)
This study aims to describe family support and self-efficacy with student resilience in completing thesis. This study uses a correlational descriptive quantitative method. The population of this study were 442 undergraduate students at the Faculty of Education who were active in 2018, with a sample of 210 people, who were selected using a proportional stratified random sampling technique. The instruments used were family support questionnaires and self-efficacy questionnaires. Analyzed with descriptive statistics, simple regression and multiple regression. The results of this study indicate that (1) family support is generally in the good category with an average score of 180.50 with a percentage of respondents of 72.20%,